Vẽnh Jykre si: memória, tradição e costume entre os Kaingang da T.I.- Faxinal - Cândido de Abreu-Pr - Rodrigues, Isabel Cristina (2012)
This thesis is dedicated to the research of the relationship between memory, traditions and customs amongst a people, the Jê Meridional: the Kaingang of the Indigenous Land Faxinal, located in the municipality of Candido de Abreu, PR. The theoretical path which governs this study, makes its trail through historical and anthropological discussions in order to affirm that, the traditions of a people should be recognized- as the invention and reinvention of cultural practices, stemming from distinct origins which undergo constant renovations and redefinitions, resulting from the dynamics of history and daily life. The focus of analysis is centered on the way the Kaingang have developed their knowledge and practices, and reaffirmed their ethnical belonging in the relations they have come to establish in their world as well as in the world of the fog (whites), in other words, how they have build their territorialities